Interculturalidad en licenciaturas indígenas brasileñas (2021)
This article presents reflections on interculturality in indigenous undergraduate programs in Brazil, based on the results of a PhD research on Latin American indigenous undergraduate programs, whose objective is to identify the challenges and potentialities of these experiences. For this work, six programs from different Brazilian regions are analyzed. The research follows a qualitative methodological approach of ethnographic nature, covering a set of strategies, such as participant observation, unstructured dialogues, semistructured interviews, and documentary research. The results show the presence of intercultural aspects in the form of challenges and potentialities. The challenges of interculturality are related to a variety of factors, such as the colonial structure of thought, still prevalent in universities and in Brazilian society; the difficulties of relations between different cultures; the complexity of indigenous demands, especially in a national political context that does not favor these topics; and the differences between ethnic groups. The potentialities reveal the creation of intercultural pedagogical strategies that contribute to interdisciplinarity, ethnosciences, integration between theory and practice, the use of different artistic languages, and the creation of different research methods, generating new knowledge and pedagogical materials, which implies a linguistic, political, and cultural strengthening.